A study on Antitumor Effect of 1, 2, 4-Thiadiazole Derivatives in Liver and Breast Cancer Cell Lines Hep G2 by Using (HCS) Technique - Mahdi, Sarah A (Al-Nahrain Journal of Science, 2017)
Multi-parametric investigation of composite poisoning at the level of specific cells, by using cellular and pour cytometry showing constructed tactics for example high-content screening, play key roles to find the poisoning and arrangement of components deepened on notice forms reversible and irreversible cellular disadvantage. To probe the effect of 1,2,4-triazole derivative cultured cellular model (liver carcinoma cell line) using HCS, this work was achieved. By an induction of apoptosis, with cells then was tested by Annexing V spotting and cell decrease as demonstrated .The products indicated that the derivative lead in the disturbance of membrane mitochondrial potential (MMP), cell tissue perviousness, nuclear abbreviation, shatter and freedom for cytochrome c of the mitochondrial addicted on cytosol. This finding suggests that derivative is a potential liver carcinoma inhibitor matched to doxorubicin as affirmative control. Also the data indicated that 1,2,4-triazole derivative possibly will have therapeutic importance in liver cancer treatment which value more development.